The Concept of Jihad In Ṣaḥiḥ Ạl-Bukhari’s Kitab Ạljihad Wa Ạl-Siyar: A Critical Examination of Extremist Arguments - Noratikah Binti Che Yusof (Universiti Sains Islam Malaysia, 2025)
Matric: 3191308 (FPQS)